Unusual Initial Abdominal Presentations of Invasive Meningococcal Disease. (28th March 2018) - Guiddir, Tamazoust; Gros, Marion; Hong, Eva; Terrade, Aude; Denizon, Mélanie; Deghmane, Ala-Eddine; Taha, Muhamed-Kheir
Abstract : Early abdominal presentations of invasive meningococcal disease are increasingly reported. Our work increases the awareness of these forms by clinicians. Rapid management should reduce the high fatality rate that is associated with these presentations and avoid unjustified interventions (eg, appendectomy). Abstract: Background: Invasive meningococcal disease (IMD) is recognized as septicemia and/or meningitis. However, early symptoms may vary and are frequently nonspecific. Early abdominal presentations have been increasingly described. We aimed to explore a large cohort of patients with initial abdominal presentations for association with particular meningococcal strains. Methods: Confirmed IMD cases in France between 1991 and 2016 were screened for the presence within the 24 hours before diagnosis of at least 1 of the following criteria (1) abdominal pain, (2) gastroenteritis with diarrhea and vomiting, or (3) diarrhea only. Whole-genome sequencing was performed on all cultured isolates. Results: We identified 105 cases (median age, 19 years) of early abdominal presentations with a sharp increase since 2014. Early abdominal pain alone was the most frequent symptom (n = 67 [64%]), followed by gastroenteritis (n = 26 [25%]) and diarrhea alone (n = 12 [11%]). Twenty patients (20%) had abdominal surgery. A higher case fatality rate (24%) was observed in these cases compared to 10.4% in all IMD in France ( P = .007) with high levels of inflammation markers in the blood. Isolates of group W were significantly more predominant in these cases compared to all IMD. Most of these isolates belonged to clonal complex 11 of the sublineages of the South American-UK strain. Conclusions: Abdominal presentations are frequently provoked by hyperinvasive isolates of meningococci. Delay in the management of these cases and the virulence of the isolates may explain the high fatality rate. Rapid recognition is a key element to improve their management.